2021
DOI: 10.3390/biomedicines9050471
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression in Extracellular Vesicles from Nasal Lavage Fluid in Chronic Rhinosinusitis

Abstract: Extracellular vesicles (EVs) are nanovesicles of endocytic origin released by cells and found in human bodily fluids. EVs contain both mRNA and microRNA (miRNA), which can be shuttled between cells, indicating their role in cell communication. This study investigated whether nasal secretions contain EVs and whether these EVs contain RNA. EVs were isolated from nasal lavage fluid (NLF) using sequential centrifugation. EVs were characterized and EV sizes were identified by transmission electron microscopy (TEM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…24 MiRNAs can be transferred by exosomes, and generally function by binding target mRNA transcripts and regulating the cellular response pathways. 33 EV-derived miRNAs were reported to be differentially expressed between chronic rhinosinusitis and healthy controls in nasal lavage fluid, suggesting that they might be involved in the 34 In the present study, we sequenced the serum exosomal miRNAs in pediatric AR patients under SCIT. The results indicated that exosomal miRNAs were differentially expressed between the effective and ineffective groups.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…24 MiRNAs can be transferred by exosomes, and generally function by binding target mRNA transcripts and regulating the cellular response pathways. 33 EV-derived miRNAs were reported to be differentially expressed between chronic rhinosinusitis and healthy controls in nasal lavage fluid, suggesting that they might be involved in the 34 In the present study, we sequenced the serum exosomal miRNAs in pediatric AR patients under SCIT. The results indicated that exosomal miRNAs were differentially expressed between the effective and ineffective groups.…”
Section: Discussionmentioning
confidence: 89%
“… 33 EV-derived miRNAs were reported to be differentially expressed between chronic rhinosinusitis and healthy controls in nasal lavage fluid, suggesting that they might be involved in the pathomechanism of upper airway inflammatory diseases. 34 In the present study, we sequenced the serum exosomal miRNAs in pediatric AR patients under SCIT. The results indicated that exosomal miRNAs were differentially expressed between the effective and ineffective groups.…”
Section: Discussionmentioning
confidence: 99%
“…The verification of full-texts excluded five articles as they were out of topic. As a result of the described search procedure, 17 articles that met all inclusion criteria were retrieved [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research by Cha et al revealed that the expression of extracellular vesicles miRNA differed depending on the chronic phenotype of non-nasal sinusitis (CRSsNP) and chronic nasal polyposis sinusitis (CRSwNP). By transferring a miRNA from one cell to another, EVs can play a functional role in CRS development [ 54 ].…”
Section: Discussionmentioning
confidence: 99%